Penerapan Teknik Vertikultur Berbahan Bambu sebagai Upaya Adaptasi Tanaman Obat Keluarga (TOGA) Terhadap Banjir di Desa Ngablak - Al Irvan, Setyo Wahono; Farahdiansari, Ardana Putri; Anam, Ahmad Qoirul; Prayitno, Muhammad Edi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2026)
Ngablak Village in Dander Subdistrict, Bojonegoro Regency, is a flood-prone area due to the annual overflow of the Bengawan Solo River. This condition hinders the community, especially traditional herbal medicine artisans, in cultivating Family Medicinal Plants (TOGA) as the main raw material. Through a community service program, the PPK Ormawa UKM P2J team from Universitas Bojonegoro introduced an agricultural innovation using a bamboo-based verticulture system as an environmentally friendly and flood-adaptive solution. The activities included site surveys, coordination with village officials, socialization, training, hands-on practice in planting TOGA, as well as monitoring and evaluation. The results show that verticulture not only reduces the risk of crop damage caused by flooding but also utilizes the abundant local bamboo resources that are often underutilized. Participants gained practical skills in constructing, maintaining, and applying verticulture media, enabling them to implement it independently. This program provides Ngablak villagers, particularly herbal medicine artisans, with an alternative solution to ensure sustainable raw material availability. In conclusion, bamboo-based verticulture can enhance community self-reliance, strengthen traditional herbal enterprises, and support local economic resilience in flood-prone areas.